Transcutaneous CO2 versus end-tidal CO2 in neonates and infants undergoing surgery: a prospective study - Chandrakantan A (Dove Medical Press, 2019)
Arvind Chandrakantan,1 Ronald Jasiewicz,2 Ruth A Reinsel,3 Kseniya Khmara,2 Jonathan Mintzer,4 Joseph D DeCristofaro,4 Zvi Jacob,2 Peggy Seidman51Department of Anesthesiology & Pediatrics, Texas Children’s Hospital, Houston, TX, USA; 2Department of Anesthesiology, Stony Brook University Hospital, Stony Brook, NY, USA; 3Department of Neurology, Stony Brook University Hospital, Stony Brook, NY, USA; 4Department of Neonatology & Pediatrics, Stony Brook University Hospital, Stony Brook, NY, USA; 5Department of Anesthesiology & Pediatrics, UH Rainbow Babies and Children’s Hospital, Cleveland, OH, USAAim: End-tidal CO2 (EtCO2) is the standard in operative care along with pulse oximetry for ventilation assessment. It is known to be less accurate in the infant population than in adults. Many neonatal intensive care units (NICU) have converted to utilizing transcutaneous CO2 (tcPCO2) monitoring. This study aimed to compare perioperative EtCO2 to tcPCO2 in the pediatric perioperative population specifically below 10 kg, which encompasses neonates and some infants.Methods: After IRB approval and parental written informed consent, we enrolled neonates and infants weighing less than 10 kg, who were scheduled for elective surgery with endotracheal tube under general anesthesia. PCO2 was monitored with EtCO2 and with tcPCO2. Venous blood gas (PvCO2) samples were drawn at the end of the anesthetic. We calculated a mean difference of EtCO2 minus PvCO2 (Delta EtCO2), and tcPCO2 minus PvCO2 (Delta tcPCO2) from end-of-case measurements. The mean differences in the NICU and non-NICU patients were compared by t-tests and Bland–Altman analysis.Results: Median age was 10.9 weeks, and median weight was 4.4 kg. NICU (n=6) and non-NICU (n=14) patients did not differ in PvCO2. Relative to the PvCO2, the Delta EtCO2 was much greater in the NICU compared to the non-NICU patients (−28.1 versus −9.8, t=3.912, 18 df, P=0.001). Delta tcPCO2 was close to zero in both groups. Although both measures obtained simultaneously in the same patients agreed moderately with each other (r =0.444, 18 df, P=0.05), Bland–Altman plots indicated that the mean difference (bias) in EtCO2 measurements differed significantly from zero (P<0.05).Conclusions: EtCO2 underestimates PvCO2 values in neonates and infants under general anesthesia. TcPCO2 closely approximates venous blood gas values, in both the NICU and non-NICU samples. We, therefore, conclude that tcPCO2 is a more accurate measure of operative PvCO2 in infants, especially in NICU patients.Keywords: infant, newborn, end-tidal CO2, blood gas monitoring-transcutaneous, intensive care monitoring- neonatal, ASA monitoring standards